Oral health education in schools: promoting health agents - Garbin, Clea Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; dos Santos, K. T. [UNESP]; Lima, D. P. [UNESP] (Wiley-Blackwell, 2009)
Purpose: The aim of this study was to verify the influence of preschool children participating in an oral health education programme on daily health practices of their families, through parent's perception. Methods: A sample of 119 parents of 5- to 6-year-old preschool children were selected. Data were collected using a structured open-closed questionnaire, self-administered. The questions focused on parents' knowledge about activities of oral health education conducted in school, the importance given by them to these activities, learning from their offspring and the presence of habit change at home. Results: In total, 63 (52.9%) parents agreed to participate. Ninety-eight per cent knew about educative and preventive activities developed at school and all of them affirmed that these activities were important, mainly because of knowledge, motivation and improvement in children's health. Ninety and half per cent of parents reported that they learned something about oral health from their children and, among these, almost half (47.8%) cited toothbrushing as the indicator for better learning. Besides this, 87.3% of participants revealed the change in oral health habits of their family members. Conclusion: Preschool children were able to transmit knowledge acquired at school to their parents that included change in oral health routine of their family members.
Keywords: dental health education; health promotion; preschool child; preventive dentistry